Effects of climate and food availability on four rodent species in Southeastern Brazil - Bergallo, H. G. (Journal of Mammalogy, 2020)
Seasonal reproduction of small mammals in the tropics usually is related to annual cycles of rainfall. We examined effects of weather and food availability on reproduction and population ecology of Nectomys squamipes, Oryzomys intermedius, Akodon cursor and Trinomys iheringi. Each species was studied monthly from February 1993 to January 1995 using mark-recapture methods at Ilha do Cardoso, São Paulo State, Brazil. Average capture rate for each month was used as an index of population size, and survival rate was estimated by the Jolly-Seber method. Direct effects of food availability and rainfall were related to female reproductive activity and survival rate. Path analyses were used to describe quantitatively the hypothesized causal relations among the variables. N. squamipes reproduced seasonally, and O. intermedius, T. iheringi, and A. cursor reproduced all year with peaks during the rainy season. Species responded differently to the environmental factors; however, food availability seems to be the main factor determining reproduction. Abundance of rains appears to diminish survival rate of O. intermedius. Survival rate of N. squamipes increases with increases in fruit availability.